Pengembangan Prototipe Alat Sortir Berdasarkan Warna Berbasis Internet of Things (IoT) Menggunakan Thingspeak - Imron, Ali; Anggai, Sajarwo (Universitas Pamulang, 2024)
Manual sorting processes in the agriculture and manufacturing industries often require significant costs, time, and labor, impeding production efficiency and increasing the risk of errors. The proposed solution is to utilize an automated sorting device based on the color of the objects. This sorting prototype was developed using IoT technology with the ThingSpeak platform through a Research and Development method. The development steps included needs analysis, system design, prototype implementation, testing, and performance evaluation. The prototype incorporates a TCS 3200 color sensor, Nodemcu ESP8266 IoT module, servo motor, and the ThingSpeak platform. Testing was conducted using red, green, orange, and black objects. The test results demonstrated that the prototype achieved high accuracy in color identification, rapid data processing response, and consistent data transmission to ThingSpeak. The prototype was successfully developed according to the plan. Performance evaluation indicated its effectiveness in supporting color-based sorting processes in the agriculture and manufacturing industries. This prototype significantly contributes to the automation of industrial processes, particularly in using color as the primary criterion for object separation.